Development of the Brief Social Capital for Youth Sexual and Reproductive Health Scale: Exploratory and Confirmatory Factor Analysis. Issue 4 (May 2019) - Córdova, David; Coleman-Minahan, Kate; Bull, Sheana; Borrayo, Evelinn A.
Social capital plays an important role in sexual and reproductive health among youth, yet few measures to assess this concept have been developed and tested for this population. We developed and examined the factor structure of the Brief Social Capital for Youth Sexual and Reproductive Health Scale. Drawing on the empirical literature, we identified item content to assess an overall construct of social capital in relationship to youth's sexual and reproductive health, including condom self-efficacy, civic engagement, and adult and community support. We conducted exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) with a sample of 200 youth, predominately low-income and ethnic minority in Denver, Colorado. EFA with geomax rotation yielded a three-factor solution. CFA provided an adequate model fit with acceptable standardized factor loadings. This study provides a validated measure for future research to further examine social capital and youth sexual and reproductive health.